IDENTIFIKASI MUSCULOSKLETAL DISORDERS (MSDs) PADA AKTIVITAS PEMASANGAN CERUCUK PERKUATAN PONDASI DI DAERAH RAWA GAMBUT - Roberta Zulfhi Surya; Akbar Alfa (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (LPPM), 2019)
Indraigiri Hilir has a very large peatland. Large peatland is constraint in the development of infrastructure of a region. The problems posed ini the field of contruction is the amount of land degradation and low soil carrying capacity. Therefore, an alternative to the soil reinforcement is required by using the cerucuk timber to increase the carrying capacity of the foundation and soil reinforcement. This research was conducted to determine Musculoskletal Disorders (MSDs) in instalation of piles (the cerucuk timber) using Nordic Body Map Questionnaire. NBM happers due to these 28 body parts are ini direct contact with the activities. The primary cause of MSDs is unnatural working attitude and exessive mucle tension began from design of a working system that is designed not ini accordance with the workers’ limitation